Cough-Aerosol cultures of Mycobacterium tuberculosis in the prediction of outcomes after exposure. A household contact study in Brazil - Acuña-Villaorduña, Carlos (2018)
Background Mycobacterium tuberculosis cultures of cough-generated aerosols from patients with pulmonary tuberculosis (TB) are a quantitative method to measure infectiousness and to predict secondary outcomes in exposed contacts. However, their reproducibility has not been established. Objective To evaluate the predictive value of colony-forming units (CFU) of M.Tuberculosis in cough aerosols on secondary infection and disease in household contacts in Brazil. Methods Adult sputum smear+ and culture+ pulmonary TB cases underwent a standard evaluation and were categorized according to aerosol CFU. We evaluated household contacts for infection at baseline and at 8 weeks with TST and IGRA, and secondary disease. Results We enrolled 48 index TB cases; 40% had negative aerosols, 27% low aerosols (<10 CFU) and 33% high aerosols (≥10 CFU). Of their 230 contacts, the proportion with a TST ≥10 mm at 8 weeks was 59%, 65% and 75%, respectively (p = 0.34). Contacts of high aerosol cases had greater IGRA readouts (median 4.6 IU/mL, IQR 0.02-10) when compared to those with low (0.8, 0.2-10) or no aerosol (0.1, 0-3.7; p = 0.08). IGRA readouts in TSTconverters of high aerosol cases (median 20 IU/mL, IQR 10-24) were larger than those from aerosol-negative (0.13, 0.04-3; p = o.o2). 8/9 (89%) culture+ secondary TB cases occurred in contacts of aerosol+ cases. Conclusion Aerosol CFU predicts quantitatively IGRA readouts among household contacts of smear positive TB cases. Our results strengthen the argument of using cough aerosols to guide targeted preventive treatment strategies, a necessary component of current TB elimination projections.